PERKEMBANGAN AWAL PERADILAN ISLAM (STUDI TENTANG PENERAPAN PRINSIP-PRINSIP NEGARA HUKUM) - Abdul Hafiz (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
Muslim cummunity is a part of world  communities who  dream rechtstaat or rule of law. The politic philosophers or experties have  different  opinions  about  principles which  contained by rule  of law  concept. Islam, as the  religion with it’s doctrins  on law, has  distinguish  concept of rule of law. Islamic  rule of law is a variant of rule of law concepts. After studying some literatures, it is founded that Islamic rule of law has some principles:  adherence, faith, equality, honouring the human right, and judge independency.